Preserving Patient's Anonymity for Mobile Healthcare System in IoT Environment - Seungsoo Baek; Seung-Hyun Seo; Seungjoo Kim (International Journal of Distributed Sensor Networks)
Emerging IoT (Internet of Things) technologies provide many benefits to the improvement of healthcare service. The successful deployment of IoT depends on ensuring security and privacy that need to adapt to their processing capabilities. IoT is vulnerable to attacks since communications are mostly wireless. So far, most researchers have only focused on security or privacy issues related to wireless communication in the IoT environment without considering all the communication vulnerabilities. However, since most of biometric data from sensors travel over the cellular network, we are required to study a privacy-enhanced scheme that covers all the secure communications. Therefore, we propose a novel privacy-enhanced mobile healthcare system in the IoT environment. Our proposed scheme provides anonymous communication between a patient and a doctor in a wireless cellular network satisfying security requirements and guaranteeing its efficiency.